Effect of morphological algorithms on medical imaging - Phan, Viet Cuong; Ho Thi, Thao; Le, Tuan Anh; Nguyen, Hong Ha; Ha, Quang Thanh (Nuclear Science and Technology, 2018)
Handling and improving the quality of medical images with the help of computer software is one of the important stages in the diagnosis and treatment. In this article, we focus on describing the new morphological algorithms by ITK (Insight Segmentation and Registration Toolkit). These morphological operators eliminate noise, detect good edges, and overcome the drawback of traditional edge detection methods.